If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2y + 2 = 11 + 9y + -1x Reorder the terms: 2 + 5x + 2y = 11 + 9y + -1x Reorder the terms: 2 + 5x + 2y = 11 + -1x + 9y Solving 2 + 5x + 2y = 11 + -1x + 9y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2 + 5x + x + 2y = 11 + -1x + x + 9y Combine like terms: 5x + x = 6x 2 + 6x + 2y = 11 + -1x + x + 9y Combine like terms: -1x + x = 0 2 + 6x + 2y = 11 + 0 + 9y 2 + 6x + 2y = 11 + 9y Add '-2' to each side of the equation. 2 + 6x + -2 + 2y = 11 + -2 + 9y Reorder the terms: 2 + -2 + 6x + 2y = 11 + -2 + 9y Combine like terms: 2 + -2 = 0 0 + 6x + 2y = 11 + -2 + 9y 6x + 2y = 11 + -2 + 9y Combine like terms: 11 + -2 = 9 6x + 2y = 9 + 9y Add '-2y' to each side of the equation. 6x + 2y + -2y = 9 + 9y + -2y Combine like terms: 2y + -2y = 0 6x + 0 = 9 + 9y + -2y 6x = 9 + 9y + -2y Combine like terms: 9y + -2y = 7y 6x = 9 + 7y Divide each side by '6'. x = 1.5 + 1.166666667y Simplifying x = 1.5 + 1.166666667y
| 13-ln(5-x)=0 | | 7=5v-19 | | -54=7x+3x+6 | | 2x-4=(2x-9)/2 | | -12=-6j | | 2g-11(-2)=26 | | 0=-6x-2x-8 | | Dy=Cx | | 4/3t=5/2 | | -6x-9+2x=39 | | (3t^2-t-4)(4t^2+3t-1)= | | 2x+5+3x=-25 | | 3(13+5.5k)=6k+18 | | 33=-4x-3x-2 | | -2-3x-4x=33 | | Cot^4x-1=0 | | 2-3x-4x=33 | | 2x^2+6y^2=13 | | 49/7p-49 | | 4[lnz+ln(z+5)]-2ln(z-5)= | | h=-16t*t+128t | | 4+6x+6x=-44 | | 1+7x+2x=109 | | 7(c-9)=9(2c-8)-4c | | 9x^6y^10/x^0Y^9 | | y=a^8+cos^8x | | n=c-m | | 3t+nt=y | | -4x+9+5x=18 | | 56=7/8v | | 10=(1/6)x | | 2x-5+5x=-54 |